Change in the Affixation Meaning in Animation Film Entitled ‘Bilal: A New Breed of Hero’ (Semantic Analysis) - Fernanda Venturini Nur Salimova (Universitas Islam Negeri Sunan Kalijaga, 2022)
Bilal: a New Breed of Hero is a film produced by Barajoun Entertainment and released in 2015 in Arabic and English. This study aims at identifying the meaning change of Arabic affixation occurring in the film. The theory used is Chaer's theory of meaning change in semantic studies. The study used a descriptive qualitative method on depictions that can provide an objective picture and the tenique Meanwhile, the researchers used listening and taking notes to collect the data. The collected data were then analyzed using a semantic approach, especially affixation consisting of meaning change and the factors that influence it. The results showed that the Bilal film: A New Breed of Hero conveys five meaning changes. Those changes are broadening, narrowing, total change, euphemism, and dysphemism. As for two factors, linguists and non-linguists, influence the change in meaning. The results found in this study which consists were 52 research data consisting of 16 the amount of broadening data (30,8%), 18 of narrowing data (34,6%), 10 of total change data (19,2%), 5 of euphemism data (9,6%), and 3 of dysphemism data (5,8%).